2022
DOI: 10.1002/ccr3.5611
|View full text |Cite
|
Sign up to set email alerts
|

Doege–Potter syndrome due to endothoracic solitary hypoglycemic fibrous tumor

Abstract: Doege–Potter syndrome leads to severe and sustained symptomatic hypoglycemia and is associated with the solitary fibrous tumor. It is a rare cause, and its diagnosis requires a clinical suspicion and other markers such as insulin‐like growth factor II. Here, we describe a case of a patient with intrathoracic tumor and hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In rare cases, the tumor can also produce symptoms such as hemorrhage, digital clubbing, hypertrophic pulmonary osteoarthropathy and hypoglycemia. When SFTP secretes excessive insulin-like growth factor II (IGF-2), it can cause a rare recurrent hypoglycemia called Doege–Potter syndrome ( 10 ). These symptoms usually gradually disappear after tumor resection, but they could reappear when tumor recurs ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases, the tumor can also produce symptoms such as hemorrhage, digital clubbing, hypertrophic pulmonary osteoarthropathy and hypoglycemia. When SFTP secretes excessive insulin-like growth factor II (IGF-2), it can cause a rare recurrent hypoglycemia called Doege–Potter syndrome ( 10 ). These symptoms usually gradually disappear after tumor resection, but they could reappear when tumor recurs ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports highlight the importance of SFT associated with Doege-Potter syndrome [4,[13][14][15], showing no differences between benign and malignant cases and that all end up in surgery as an effective treatment [16]. Surgical activities use images such as CT as an aid tool and can benefit from 3D modeling by allowing us to approximate the actual size of the tumor, as seen in other medical areas [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted an exploratory comparative study using Dycom CAT data from a recently reported patient with SFT [4]. A 74-year-old man with SFT and hypoglycemia (38 mg/dl) was admitted to hospital with chest pain for two weeks.…”
Section: Study Design and Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a fibrous tumor in the mediastinum that manifests as hypoglycemia in 1930. 4 DPS is a rare paraneoplastic syndrome with an incidence of less than 5% and manifests as hypoglycemia. 5 DPS presents hyperinsulinemic hypoglycemia from the ectopic secretion of insulin-like growth factor II (IGF-II) from the non-islet cell from a solitary fibrous tumor.…”
Section: Introductionmentioning
confidence: 99%